Chart exhibiting the discoveries of the second American-Grinnell-Expedition in search of Sir John Franklin : unrevised from the original material and projected on the spot / E.K. Kane - Kane, Elisha Kent, 1820-1857; United States. Congress (34th, 1st session : 1855-1856). Senate; Ackerman Lithr.; (Ackerman Lith., 1855)
Deposited Nov. fifteenth, 1855 Relief shown by hachures.; "Senate Ex. Doc. No. 1, 1st Session, 34th Congress." Removed from AGSL's copy of: "Message from the President of the United States to the two houses of Congress at the commencement of the first session of the thirty-fourth congress, part IV, Illustrations belonging to reports accompanying the message, 1856." Grayscale;